Leveraging Resilience-supportive Strategies to Enhance Protective Factors in Young Sexual Minority Men: A Scoping Review of HIV Behavioral Interventions Implemented in High-income Countries. Issue 8 (13th October 2022) - Meanley, Steven; Sexton Topper, Patrina; Listerud, Louis; Bonett, Stephen K.; Watson, Dovie; Choi, Seul Ki; Teixeira Da Silva, Daniel; Flores, Dalmacio D.; James, Richard; Bauermeister, José A.
ABSTRACT: Behavioral HIV interventions focused on strengthening young sexual minority men's (SMM) internal (assets) and external (resources) protective factors are promising, yet their evaluation as resilience-supportive strategies to minimize or negate HIV-related risks remain understudied. The objective of this scoping review was to describe resilience-supportive intervention strategies that have been used to achieve desired HIV behavioral outcomes and to identify how these strategies have been evaluated using a resilience analytic framework. Our scoping review uncovered 271 peer-reviewed articles, of which 38 were eligible for inclusion based on our review criteria. The majority of interventions relied on social support strategies as their primary resilience-supportive strategy. A third of interventions reviewed analyzed their findings from a deficits-focused model, another third used compensatory resilience models, and the remaining interventions employed a hybrid (i.e., deficit and compensatory model) strategy. None of the interventions evaluated their intervention effects using a risk-protective model. From our synthesis regarding the current state of research around resilience-informed interventions, we propose strategies to inform the design of resilience-supportive approaches and make recommendations to move the field forward on how to develop, implement, and measure young SMM's resiliency processes.